2020
DOI: 10.1016/j.clnesp.2020.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of malnutrition in hospitalized COVID-19 patients

Abstract: Background & aims Nutritional knowledge in patients with SARS-Cov2 infection (COVID-19) is limited. Our objectives were: i) to assess malnutrition in hospitalized COVID-19 patients, ii) to investigate the links between malnutrition and disease severity at admission, iii) to study the impact of malnutrition on clinical outcomes such as transfer to an intensive care unit (ICU) or death. Methods Consecutive patients hospitalized in a medicine ward at a university hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
193
3
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(223 citation statements)
references
References 19 publications
13
193
3
14
Order By: Relevance
“…They found that 42% of hospitalized patients with COVID‐19 were at risk of malnutrition and 28% of these patients were considered malnourished at the time of assessment 5,6 . Another study in 114 consecutive, hospitalized COVID‐19 patients found similar results using the Global Leadership Initiative on Malnutrition (GLIM) criteria with 42% (48/114 patients) being malnourished 7 …”
Section: Malnutrition Frequency In Covid‐19mentioning
confidence: 87%
See 1 more Smart Citation
“…They found that 42% of hospitalized patients with COVID‐19 were at risk of malnutrition and 28% of these patients were considered malnourished at the time of assessment 5,6 . Another study in 114 consecutive, hospitalized COVID‐19 patients found similar results using the Global Leadership Initiative on Malnutrition (GLIM) criteria with 42% (48/114 patients) being malnourished 7 …”
Section: Malnutrition Frequency In Covid‐19mentioning
confidence: 87%
“…Secondly, malnutrition is frequently seen in COVID‐19 patients 5‐7 . Disease‐associated reductions in food intake and malnutrition can contribute to tissue wasting.…”
Section: Weight Loss During Covid‐19mentioning
confidence: 99%
“…Abhängig vom verwendeten Screening-Instrument liegt die Prävalenz der Mangelernährung bei etwa 50 % [ 66 ]. Bei Anwendung der neuen Diagnosekriterien der Global Leadership Initiative on Malnutrition (GLIM) ist bei 42–50 % der COVID-19-Patienten eine Malnutrition zu diagnostizieren [ 3 , 50 ]. In einer italienischen Studie verloren 29 % der COVID-19-Patienten während des Krankheitsverlaufs mehr als 5 % ihres Körpergewichts [ 12 ].…”
Section: Die Rolle Der Ernährungunclassified
“…Bedock reported that 42.4% of 114 French hospitalized Covid 19 patients were malnourished. 2 Wei reported that 86.2% of 348 Hospitalized Chinese Covid 19 patients were malnourished (39.9 % moderate to severe malnutrition, 46.3% mild malnutrition). 3 …”
Section: Covid 19 Malnutrition Commonmentioning
confidence: 99%